Tuberculosis Surveillance in Dushanbe: a Way Forward to Strengthening - А. А. Sidzhotkhonov; Z. Kh. Tilloeva; N. Dzh. Dzhafarov; А. А. Amirzoda; B. P. Pirmakhmadzoda; D. А. Nabirova (Туберкулез и болезни лёгких)
The objective: to evaluate the current tuberculosis surveillance system in Dushanbe for each of the following parameters: simplicity, flexibility, acceptability, sensitivity, and promptness of response; to provide recommendations to improve the system.Methods. The tuberculosis surveillance system was evaluated in the city of Dushanbe in April-May 2021 using updated guidelines of the Center for Disease Control and Prevention for evaluating public health surveillance systems, 2006.Result: The system fulfills its goals and objectives, but has gaps in promptness of response, acceptability and representativeness.Conclusions. The tuberculosis surveillance system needs to be improved and requires professional development training of family medicine workers, TB specialists, and epidemiologists.